EVALUASI TERHADAP SISTEM PENCATATAN AKUNTANSI PADA USAHA MIKRO, KECIL DAN MENENGAH (Studi Kasus di Kota Semarang) - Tegar Satriyo Notohatmodjo; Endang Kiswara (Diponegoro Journal of Accounting, 2014)
This study aims to analyze how the needs and understanding and provide practical guidance in making the accounting system of Small and Medium Enterprises. This guidance is expected to be used to construct a model of accounting records customized from Accounting Standards - Entities Without Public Accountability (SAK-ETAP).This research was conducted with qualitative methods through case studies  with small medium enterprises in Semarang City as the population and thirty Small and Medium Enterprises in  Semarang City as the samples, by interviewing the owners of each of these Enterprise, and do literature studies for articles, books, journals and materials another supported this research.Results of this study showed that most of the Small and Medium Enterprises in the Semarang City is still not understood and considered accounting system as a difficult thing. But these Enterprises agree on the importance of accounting system and are interested in learning about the learning resources accounting system that is easy to use.